FILSAFAT ILMU PENGETAHUAN KITAB SUCI WEDA - Ketut Bali Sastrawam (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2018)
Vedas are scriptures, which have been the highest source of Hinduism. In it is taughtvarious knowledge: science (requires rational and empirical); philosophy (requires only rational),and mystical knowledge, (non rational but empirical). Every knowledge in the Vedas has theessence; in fact, the Vedic scriptures explain so much science that its truth can be provenscientifically. Thus, the wise man said that, What is in the Vedas, is not necessarily found inmodern science, on the contrary, what exists in modern knowledge is certainly present in theVedic scriptures. This paper is a literature study product, so it is not possible to describe thescience of weda as a whole. The reading of some literature finds that, the Vedic scriptures havea separate philosophy called the philosophy of science. In conclusion, the Vedic scriptures havea philosophy of science.